(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the word formation structure of complex and complexabbreviated names of the nouns which have arisen in the Ukrainian language lately. As a material of research the publicistic and information texts of the newspaper " Ukraine is young " for 2005-2006 years. The ways of formation of new lexicon in mass media in the certain degree reflect the tendencies of modern newformation as a whole.